THE SHANGHAI COOPERATION ORGANIZATION: OPPORTUNITIES FOR RUSSIA - STARCHAK, Maxim (CENTRAL ASIA AND THE CAUCASUS, 2011)
The striving of the People’s Republic of China (PRC) for leadership is being increasingly manifested within the framework of the Shanghai Cooperation Organization (SCO), which plays an important role on the world political arena. After transformation of the Shanghai Six into a regional organization, China, with the aim of further increasing its political and economic influence in the region, was able to insist on the organization’s secretariat being located in Beijing.In order to achieve its goals, the PRC is taking the following steps within the framework of the SCO:—strengthening trade relations with the Central Asian states granting them multibillion loans;—exerting active efforts to gain a stronger foothold in the oil and gas fields of Central Asia;—skillfully using the SCO in the fight against separatism in the XUAR;—actively preventing the spread of U.S. influence in Central Asia;—implementing educational programs for the young people of the Central Asian countries.By continuing to reinforce its position in the region and in the SCO, China is trying to acquire the status of the organization’s informal leader.1However, despite China’s activity, Russia, which is pursuing its own national interests in the region engendered by the historical close ties that have developed with the Central Asian countries, also has every opportunity to significantly increase its influence in the SCO.